Mental Toughness in Female Athletes: “Does It Differ from Female Musicians?” - Muhamad Galih Firzatulloh; Mohammad Zaky; Septian Williyanto (Universitas Negeri Semarang, 2025)
This study tried to probe possible differences in mental toughness between female musicians and female athletes as an approach toward better understanding the concept of psychological resilience across different performance contexts. The sample population consisted of sixty females from Universitas Pendidikan Indonesia: thirty athletes coming from the Faculty of Sports and Health Education (Faculty of Sports and Health Education) and another group of thirty musicians belonging to the Faculty of Art and Design Education (FPSD). Data were collected through the use of the Mental Toughness Questionnaire 18 (MTQ18) which duly described emotional control, self-belief, motivation, confidence, and challenge. Above all other specific requisites, this instrument rated high with excellent construct and content validity in earlier studies. A descriptive comparison analysis showed that musicians were less mentally tough overall (M = 58.80, SD = 3.68) than athletes (M = 64.50, SD = 5.24). It is in the motivation and emotional control components where the widest gaps are seen-with higher internal drive and better emotional regulation among athletes. Much more slightly tilted toward the athlete’s side, the ratings of challenge between the two groups were almost identical. Results of this study support a claim that performing arts environments develop less psychological flexibility compared to controlled competitive sports environments because artistic domains emphasize creativity and expression. This study enhances understanding of the psychological rigidity of women and at the same time helps offset the gender bias that has informed past studies. Practical ramifications include the development of domain-specific mental training programs, for example, goal-setting and stress management training for athletes as well as emotional control techniques for musicians which can be derived from this study. Limitations include a small sample size based on self-reported data without subgroup analysis. More comprehensive studies with larger samples composed of different groups are required in addition to long-term studies to trace the development of mental toughness in various fields of performance.